2017
DOI: 10.1007/s11664-017-5607-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermoelectric Properties of Nanostructured Nominally Stoichiometric Pb1−x Bi x Te Prepared by Mechanical Alloying

Abstract: In this work we investigate the influence of bismuth substituted for lead in lead telluride. The material was nanostructured by mechanical alloying (MA) and was compacted via short term sintering (STS) and, alternatively, hot pressing (HP). Syntheses of samples with substitution up to 6 at.-% of bismuth were carried out twice to ensure reproducibility. All relevant thermoelectric transport parameters were measured in a wide temperature range from 123 K and 173 K, respectively, to 773 K. Two different technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The two additional reflections noticed around the plane (015) are due to the unveiling of twining orientations [19,20]. A systematic decrease in the crystallite size has been found with decreasing lattice parameters (Table 1), which is reported to be because of Sn atoms non-intercalation through Van der Waals interlayer [21]. The crystallite size is determined using the Williamson-Hall formula [16].…”
Section: Resultsmentioning
confidence: 99%
“…The two additional reflections noticed around the plane (015) are due to the unveiling of twining orientations [19,20]. A systematic decrease in the crystallite size has been found with decreasing lattice parameters (Table 1), which is reported to be because of Sn atoms non-intercalation through Van der Waals interlayer [21]. The crystallite size is determined using the Williamson-Hall formula [16].…”
Section: Resultsmentioning
confidence: 99%
“…This secondary phase could be caused by tellurium volatilization, as reported by Falkenbach et al, and the same peak can be observed in Joint Committee on Powder Diffraction Standards (JCPDS) PDF 15-0820. 14 Figure 6 shows a graph of the bulk density of the Bi 2 Te 2.7 Se 0.3 pellet according to the heating rate during rapid sintering. The Bi 2 Te 2.7 Se 0.3 pellets showed a density of about 5.52 g/cm 3 when sintered at 570°C for 10 min at heating rate of 10°C/min, conditions commonly used in pressureless sintering.…”
Section: Resultsmentioning
confidence: 99%
“…1(c)]. 114 Under applied high pressure above 5.5-7 GPa, this phase undergoes a phase transition to an orthorhombically distorted structure of Pnma symmetry. [56][57][58][59]115,116 Although this transition has been discovered a long time ago, 76,117-122 and high-pressure effects on the electronic band structure of PbTe and its parameters were investigated in a plenty of studies, 48,49,51,53,54,63,64,[123][124][125][126] the pressure-driven reconstructions of the band structure of PbTe in both the NaCl and Pnma phases remain obscure to the date.…”
Section: B Pbtementioning
confidence: 99%